2023
DOI: 10.3390/biomedicines11092483
|View full text |Cite
|
Sign up to set email alerts
|

Purified Serum IgG from a Patient with Anti-IgLON5 Antibody Cause Long-Term Movement Disorders with Impaired Dopaminergic Pathways in Mice

Yining Gao,
Hongxia Li,
Huoqing Luo
et al.

Abstract: Background: Anti-IgLON5 disease is a rare autoimmune disease of the central nervous system. It typically manifests as a chronic condition, characterized by cognitive impairments, movement disorders, and sleep disorders. The mechanisms underlying movement disorders in this disease remain poorly understood due to a lack of research. Furthermore, this disease exhibits both neuroimmune and neurodegenerative characteristics. The objective of this study is to explore the underlying mechanisms of movement disorders c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Our results suggest that IgLON5 has a physiological role in fine motor coordination and balance; these findings support the possibility that IgLON5 autoantibodies can interfere with IgLON5's function and may be pathogenically involved in the gait instability frequently noted in this disorder. This is also consistent with the results of a recent study of passive antibody transfer where intracerebral injections of IgLON5-IgG from patients into the nigrostriatal dopaminergic pathway of mice produced sustained motor impairment (22). Behavioral studies reported in KOs of other IgLON family members did not describe deficits in balance or motor coordination (27-30) (Table 2).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results suggest that IgLON5 has a physiological role in fine motor coordination and balance; these findings support the possibility that IgLON5 autoantibodies can interfere with IgLON5's function and may be pathogenically involved in the gait instability frequently noted in this disorder. This is also consistent with the results of a recent study of passive antibody transfer where intracerebral injections of IgLON5-IgG from patients into the nigrostriatal dopaminergic pathway of mice produced sustained motor impairment (22). Behavioral studies reported in KOs of other IgLON family members did not describe deficits in balance or motor coordination (27-30) (Table 2).…”
Section: Discussionsupporting
confidence: 91%
“…Despite the in vitro effects of IgLON5 antibodies, passive transfer experiments using cerebroventricular infusion or intracerebral injection of IgLON5-IgG have failed to reproduce the most characteristic symptoms of the disease and have been unable to demonstrate in vivo the pathogenic effects described in vitro (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…IgLON5 belongs to the IgLON family of cell adhesion molecules [21] and like other members of the family is spontaneously shed from the cell surface of neurons, interacting with other members of the IgLON family in cis (in the same cell) and in trans (between cells). Patient's antibodies interfere with this binding, but this potential pathogenic mechanism was not specific to IgG4 [22 ]. Second, 60% of patients present the same HLA class II haplotype (DRB1Ã10 : 01-DQB1Ã05 : 01), which is infrequent in the normal population (1-3%) [ symptoms (a feature that would be unusual in a primary neurodegenerative disease ([5 && ]).…”
Section: Insights In the Pathophysiology Of The Diseasementioning
confidence: 99%
“…Animals receiving IgLON5-IgG exhibited memory deficits, anxiety-like behaviour and progressively accumulation of human IgG immunostaining in the area of injection but the irreversible downregulation of membrane IgLON5 clusters observed in vitro was not investigated, which is a limitation [ 25 ▪ ]. Similarly, another study that injected the purified IgG into the substantia nigra pars compacta of mice for 7 days, showed a decline in motor balance that persisted 3 months after the last infusion, dopamine decrease content in the area of injection, microglial activation, and a moderate increase of p-tau measured by western blot after three months [ 26 ▪ ].…”
Section: Insights In the Pathophysiology Of The Diseasementioning
confidence: 99%